Impact and Effort of Legal Protection for Stakeholders Due to Merger Activities Islamic Banks in Indonesia - Riska Wijayanti; Septiana Na’afi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Mechanism of the merger of 3 (three) state-owned banks, PT. BRI Syariah, PT. BNI Syariah and Bank Syariah Mandiri became Bank Syariah Indonesia involving many stakeholders. Preventive measures need to be implemented to avoid violating the rules of Law and principles of corporate governance and harming stakeholders. This research aims to know the steps of merger activities against the three state-owned Islamic banks and provide information about the impact faced by stakeholders and legal protection of interested parties, especially on minority shareholders, employees/employees of Islamic banks, and customers/business partners. This research is a sociological juridical study using qualitative descriptive methods. The conclusion is to optimize legal protection for interested parties for merger activities in the banking field. Some things need to be realized. Some of these include the preparation of guidelines about sharia bank mergers made by the Financial Services Authority and the National Sharia Council for uniformity under sharia principles. The need for data migration schemes so that customers are not harmed due to system errors due to data integration and the need to harmonize employee performance with bank merger results.